Parents of ataxia‐telangiectasia patients display a distinct cellular immune phenotype mimicking ATM‐mutated patients. Issue 2 (19th October 2020) - Ogulur, Ismail; Ertuzun, Tugce; Kocamis, Burcu; Kendir Demirkol, Yasemin; Uyar, Emel; Kiykim, Ayca; Baser, Dilek; Yesil, Gozde; Akturk, Hacer; Somer, Ayper; Ozen, Ahmet; Karakoc‐Aydiner, Elif; et al.
Abstract: Background: Heterozygous relatives of ataxia‐telangiectasia (AT) patients are at an increased risk for certain AT‐related manifestations. We also show that there is an increase of infection frequency in parents of AT patients. Thus, we hypothesized that the parents might exhibit immune alterations similar to their affected children. Methods: Lymphocyte phenotyping to enumerate T‐ and B‐cell subsets was performed. Functional analyses included in vitro quantified γ‐H2AX, poly (ADP‐ribose) polymerase (PARP) and caspase‐9 proteins. Chromosomal instability was determined by comet assay. Results: We analyzed 20 AT patients (14F/6M), 31 parents (16F/15M), and 35 age‐matched healthy controls. The AT patients' parents exhibited low frequency of naive CD4 + T‐ (n = 14, 45%) and recent thymic emigrants (n = 11, 35%) in comparison with the age‐matched healthy donors. Interestingly, parents with low naive T cells also demonstrated high rate of recurrent infections (9/14, 64%). In comparison with age‐matched controls, parents who had recurrent infections and low naive T cells showed significantly higher baseline γ‐H2AX levels and H2 O2 ‐induced DNA damage as well as increased cleaved caspase‐9 and PARP proteins. Conclusion: Parents of AT patients could present with recurrent infections and display cellular defects that mimic AT patients. The observed immunological changes could be associated with increased DNA double‐strand breaks.